EFFECTIVENESS OF GOVERNMENT SUBSIDY PROGRAM IN THE TRANSITION ACCREDITATION POLICY FROM BAN PT TO LAM FOR PRIVATE UNIVERSITIES IN SURABAYA, INDONESIAN - Nuryana, Amiatun; Handoko, V. Rudy; Maduwinarti, Ayun (DIA: Jurnal Administrasi Publik, 2024)
This research was motivated by there is a policy transition from BAN PT to LAM which requires funds to support the accreditation process. This research focuses analysis effectiveness of government subsidy programs for private university in Surabaya. The method uses mix-methods and the data collection applies three techniques, namely questionnaire, interviews, documentation. Questionnaire distributed to respondents to obtain data by utilizing Google Form. The interview was carried out with the structural officials of private universities in Surabaya also documentation used to sharpen the analysis. Data analysis according to Miles and Huberman concept includes collecting data, present data, reducing data, and drawing conclusions. Based on data analysis, the effectiveness related to the presence of a government subsidy program as a solution to the transition of accreditation policy from BAN PT to LAM. The results are of the research that this government subsidy program can ease the funding burden on private universities and have positive impact.